2014
DOI: 10.1002/cssc.201300786
|View full text |Cite
|
Sign up to set email alerts
|

Origin of 5‐Hydroxymethylfurfural Stability in Water/Dimethyl Sulfoxide Mixtures

Abstract: In the present work, we combined vibrational spectroscopy with electronic structure calculations to understand the solvation of HMF in DMSO, water, and DMSO/water mixtures and to provide insights into the observed hindrance of HMF rehydration and aldol condensation reactions if it is dissolved in DMSO/water mixtures. To achieve this goal, the attenuated total reflection FTIR spectra of a wide composition range of binary and ternary mixtures were measured, analyzed, and compared to the findings of ab initio DFT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
123
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(132 citation statements)
references
References 51 publications
7
123
0
2
Order By: Relevance
“…Solvents also affect the selectivity of the reaction. DMSO is particularly selective towards 5-HMF because it suppresses the hydrolysis of 5-HMF to LA and formic acid and the humins formation [2,62], due to the strong interaction between the C=O group in 5-HMF and DMSO, which limits hydration and intermolecular condensation reactions [90]. However, there are other issues that must be considered during the choice of the solvent, such as the feasibility of its separation and recycling, its cost and its environmental effects.…”
Section: Homogeneous and Heterogeneous Catalysts In Organic Solventsmentioning
confidence: 99%
“…Solvents also affect the selectivity of the reaction. DMSO is particularly selective towards 5-HMF because it suppresses the hydrolysis of 5-HMF to LA and formic acid and the humins formation [2,62], due to the strong interaction between the C=O group in 5-HMF and DMSO, which limits hydration and intermolecular condensation reactions [90]. However, there are other issues that must be considered during the choice of the solvent, such as the feasibility of its separation and recycling, its cost and its environmental effects.…”
Section: Homogeneous and Heterogeneous Catalysts In Organic Solventsmentioning
confidence: 99%
“…13 In the current research, it is known to a great extent 3 that the distribution of products and in particular the selectivity toward HMF formation is highly dependent on the type (physicochemical properties) of the catalyst, reaction solvent, and temperature and development of new selective and effective protocols for this process has attracted broad research activity. [14][15][16][17] The first important issue in developing an economically and environmentally benign process for HMF formation is a green solvent in terms of easy separation, purity of the final product and low E factor [E-factor=total waste (kg)/product (kg)]. 2,18 Although from the standpoint of advance green and sustainable chemistry using water as a reaction solvent is a long-standing goal and thus often preferable, the difficulty in separating and purifying highly water soluble HMF, the higher possibility of rehydrating HMF in water, and the deactivation of the acid catalysts are important issues that need to be respected.…”
Section: Introductionmentioning
confidence: 97%
“…Though water is the most preferred solvent, experimental studies have shown that the addition of a co-solvent to water or replacing water with an alternate solvent can significantly alter conversions and selectivities in these reactions. [16][17][18][19] (ii) On the other hand, solvent can also directly participate in the reaction. (i) A solvent can either preferentially solvate an ''active'' functional group of a biomass molecule or its derivative and protect it from taking part in the reaction, thus precluding a particular reaction pathway.…”
Section: Introductionmentioning
confidence: 99%